Health Insurance Coverage, Government Payments, and Labor Allocation - Cristina Miller; Ashok K. Mishra (Institute of Labor Economics (IZA), 2022)
The aging of the farmer population has led to concern about a shortage of beginning farmers and ranchers. This study investigates the impact of health insurance coverage and participation in government and private insurance programs on off-farm labor allocation decisions of beginning farm-operator households in the United States. We use farm household-level data from the 2015 Agricultural Resource Management Survey and the simultaneous Probit estimation method to estimate our empirical model. Results show that beginning farm-operator households with health insurance coverage from off-farm jobs are 14% more likely to work off the farm. Our analysis also depicts a negative relationship between the receipt of counter-cyclical, conservation, risk management payments, and off-farm work by beginning farm-operator households.
Keywords: C34; I13; J22; J38; J43; Q12; Q18; 330; Agricultural Resource Management Survey; beginning farm-operator household; counter-cyclical payments; risk management payments; health insurance coverage; off-farm labor supply; two-stage simultaneous probit model